Inovasi Pembelajaran PAI dalam Meningkatkan Mutu Pendidikan PAI - Achmad Solichin; Masdarto Masdarto; Mustiatul Khasanah; Mishbahuddin Abbas; Heny Kusmawati; Solehudin Ma'ruf (Departement of Mathematics Education, 2023)
In today's technological era, innovation in learning is very important. The rapid development of technological progress must be utilized as best as possible by educators, especially Islamic religious educators. This paper is specifically focused on innovative ideas for learning PAI in schools in the face of disruptive innovation in the digital era. In the learning process the use of appropriate and effective technology is a must so that the learning process is not stagnant and rigid. Islamic religious education learning innovations must also be carried out immediately so that they can quickly develop in a better direction, produce quality output, especially in learning methods. The internet as an alternative medium for innovating Islamic religious education learning methods, can be done in the form of e-learning, or applications that facilitate the delivery of learning material, so that the learning process has an increasingly existence to attract attention, not be boring and can improve the quality of education. The method used in compiling this journal is a data collection method by means of library research, carried out by collecting data that is significantly related to problems related to Islamic Religious Education learning innovations to improve the quality of Islamic Religious Education in Indonesia.